Continuous And Intermittent Aerobic Training Repercussions On Psycho-Physiological Parameters In Adult Male - Jyoti Solanki; Vivek Solanki (Elementary Education Online, 2023)
The present study was conducted to assess the repercussions of Continuous and Intermittent Aerobic Training on Body Mass Index, Basal Metabolic Rate, Vo 2 Max., Selfesteem in College males. The objective of the study was to find out the repercussions of 30 minutes continuous aerobic workout and 15 minutes Intermittent Aerobic Training on Body Mass Index, Basal Metabolic Rate, Vo 2 Max., Self-esteem of sedentary male subjects for a total duration of twelve weeks. The study was formulated as an experimental design of twelve weeks training to find out the effect of two different methods of aerobic training on selected psycho-physiological parameters. The Pre- Post data was collected for the twelfth week of training. For the purpose of evaluating the effect of three different groups’ one way ANOVA was employed. There were significant mean differences in Continuous group with Control and Intermittent groups. There were no significant mean differences in Continuous group with Intermittent and Control group and Intermittent with Control group. There were significant mean differences in Continuous with Control and Intermittent with Control group. There were significant mean differences in Continuous with Control and Intermittent with Control group. The improvement in the Continuous and Intermittent group did not reflect any significant differences with respect to improvement of performance on Body Mass Index variable, groups also did not reflect any significant differences with respect to improvement of performance on Basal Metabolic Rate variable, no significant differences with respect to improvement of performance on Oxygen Consumption (VO. 2 Max) variable was observed and improvement of performance on Self Esteem variable also did not reflect any significant differences .